Solubility, mechanical and thermal properties of cassava starch-chitosan film incorporated with red cabbage extract / Norasmah Mohammed Manshor ... [et al.] - Mohammed Manshor, Norasmah; Abdul Karim, Adibah Ayuni; Ahmad Fuad, Nur Nabilah Husna; Yahya, Asdarina (Penerbit UiTM (UiTM Press), 2024)
Plastics from synthetic petroleum for food packaging raise a concern in waste disposal and food safety. Therefore, biodegradable polymers or biopolymers have emerged as a viable alternative to non-biodegradable plastics in food packaging and preservation besides protecting the environment. In this work, the aim was to develop cassava starch-chitosan film containing red cabbage extract and to determine the effect of red cabbage extract on the properties of the film. The film was prepared by casting method and the film solubility, tensile strength, elongation at break and thermogravimetric analysis (TGA) were determined. The solubility of cassava starch-chitosan film was 58.3%, followed by 58.8%, 59.6% and 61.1% for cassava starch-chitosan films containing 5 ml, 10 ml and 15 ml red cabbage extract, respectively. The tensile strength of film containing 5 ml red cabbage extract was higher than cassava starch-chitosan film without red cabbage extract which are 0.533 MPa and 0.417 MPa, respectively. Meanwhile, elongation at break of the film without red cabbage extract increased from 22.20% to 30.33% with the increased of red cabbage extract. From TGA, the addition of red cabbage extract caused the film to decompose at high temperature, which boosts thermal stability compared to film without red cabbage extract. Overall, this study concluded that the incorporation of red cabbage extract improved the properties of cassava starch-chitosan film which potentially be employed as an alternative material in food packaging applications.